BNC production of siwalan neer and sugarcane molasses as novel media sources - Hapsari, Dara Puspita; Perdani, Claudia Gadizza; Fahmi, Fahmi; Nurika, Irnia; Gunawan, Setiyo (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2024)
Bacterial nanocellulose (BNC) is a unique biopolymer with remarkable purity and material properties that distinguish it from plant-derived cellulose by its absence of lignin and hemicellulose. Recent research has focused on using organic waste materials as alternative substrates to reduce the cost of BNC production. This study examines the efficacy of Siwalan neer and sugarcane molasses as novel media for cultivating Komagataeibacter xylinus by comparing their performance with that of Hestrin and Schramm (HS) medium. The BNC harvested from these alternative media was rigorously characterized using scanning electron microscopy (SEM), Fourier Transform Infrared Spectroscopy (FTIR), and Thermogravimetric Analysis (TGA) to evaluate its structural and thermal properties. Notably, the use of Siwalan neer and sugarcane molasses as growth substrates enabled K. xylinus to produce BNC at a yield of 3.83 g/L, significantly exceeding the yield from the HS medium, which was 1.46 g/L. These findings highlight the potential of leveraging alternative substrates to enhance BNC production yield, cost-effectiveness, and environmental sustainability.